Digital-Based Recitation Method to Improve Senior High School Shiva Learning Achievement - Yusfira, Yusfira; Mangsi, Raya (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
This study aims to examine the implementation of the recitation method to improve PAI learning achievement. This qualitative research uses a case study approach, with primary data sources including principals, teachers, and students, as well as secondary data in the form of school documents conducted at Wajo Regency Senior High School. Data is collected through observation, interviews, and documentation, with analysis involving classification, data reduction, data presentation, and verification. The findings revealed that the design of digital-based reading methods includes selecting digital platforms, preparing interactive materials, assigning tasks based on themes, creating online discussion forums, and providing technical training for teachers and students. Its implementation utilizes technologies such as e-learning and multimedia, which have been proven to increase student motivation and learning achievement. The main challenges are limited access to technology and a lack of familiarity with digital tools, which can be overcome through intensive training, technological infrastructure improvement, and socialization of the effective use of digital tools.